2004
DOI: 10.1086/421092
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Gene Regulator Group II Polymorphism in Methicillin-Resistant Staphylococcus aureus Is Predictive of Failure of Vancomycin Therapy

Abstract: We studied methicillin-resistant Staphylococcus aureus (MRSA) isolates to determine if the group II polymorphism at the accessory gene regulator (agr) locus demonstrated any relationship with the clinical efficacy of vancomycin. One hundred twenty-two MRSA isolates from 87 patients treated with vancomycin were evaluated. Forty-five of 87 patients had no clinical or bacteriological response to vancomycin. Among the 36 clinically evaluable patients with the agr group II polymorphism, 31 had an infection that fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
196
5
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(225 citation statements)
references
References 28 publications
17
196
5
5
Order By: Relevance
“…There has not been a reported case of agr-2 CA-MRSA. Because agr-2, which seems to have benefits in surviving in the hospital setting (33), is the type frequently found in cases of HA-MRSA in South Korea (46), the absence of agr-2 in MRSA isolates reported in this study was consistent with the community origin of the isolates reported here. Compared to the MSSA isolates composed of heterogeneous pulsotypes, all the MRSA isolates were clustered into a few clones by PFGE analysis.…”
Section: Discussionsupporting
confidence: 87%
“…There has not been a reported case of agr-2 CA-MRSA. Because agr-2, which seems to have benefits in surviving in the hospital setting (33), is the type frequently found in cases of HA-MRSA in South Korea (46), the absence of agr-2 in MRSA isolates reported in this study was consistent with the community origin of the isolates reported here. Compared to the MSSA isolates composed of heterogeneous pulsotypes, all the MRSA isolates were clustered into a few clones by PFGE analysis.…”
Section: Discussionsupporting
confidence: 87%
“…Assuming that the relationship between agr function and the development of vancomycin resistance exists, it is worth noting that in one study, 48% of hospital MRSA strains were found to have reduced agr function, compared to 3.5% of community-associated MRSA strains (357), suggesting a possible higher tendency for hospital MRSA strains to develop into hVISA or VISA strains. A clinical study also linked agr group II polymorphisms with poor responses to vancomycin therapy for patients with MRSA infections (211). In addition, a loss of agr function was associated with a reduced susceptibility to platelet microbiocidal protein and reduced autolysis, a common feature of hVISA and VISA strains (295,296).…”
Section: Accessory Gene Regulator (Agr)mentioning
confidence: 99%
“…7 Low vancomycin trough levels have been implicated in the emergence of hVISA, and several studies have demonstrated a higher rate of vancomycin treatment failure, longer duration of fever, and prolonged hospitalization with hVISA and strains with elevated MIC compared to vancomycin-susceptible MRSA. [8][9][10][11][12] Until recently, vancomycin was frequently dosed to target trough levels <10 mg/L. The above concerns, combined with pharmacodynamic data suggesting that maintaining a ratio of vancomycin area under the curve to minimum inhibitory concentration (AUC/ MIC) !400 may be associated with improved clinical outcome, 13 have prompted an expert consensus to recommend targeting higher vancomycin trough levels (typically 15-20 mg/L) for invasive MRSA infections and general avoidance of trough levels <10 mg/L.…”
mentioning
confidence: 99%